Mean time: seven ways to look at time and mobility - Silva, Cidália Maria Ferreira (2016)
This paper’s idea was triggered by the exhibition “Cedric Price: Mean Time,” presented at the Canadian Centre for Architecture in Montréal. Starting with the premise that mobility is a contingent (Till, 2009) act, this text looks at the different time(s) created by this contingency. The seven time(s) here considered are: Suspending Time, Free Time, Expanding Time, Distorting time, Folded Time, Loosing time, and Living time. Through specific “spatial stories” (de Certeau, 2002) each time is explained, in their features, unfolding how time-mobility shapes the way we create different appropriations of space, transmuting not only places, but also the relationship between ourselves and the other. The faith in progress gives us the sensation of a non-stopping improvement of mobility, namely the infrastructures, systems and technology. It seems that everyday we have new ways to displace ourselves in space that are faster, and better. More speedy trains, more airplane flights, more cars, more...Nonetheless, we know that this linear time of progress is coexistent with other parallel time lines of disruption and failure. For example, the Portuguese trainroad known as “Linha do Oeste” has a long story of planned suspension attached to it: not only suffering from underinvestment and lack of maintenance but what is more with timetables that do not fit the needed working rhythms of users. All these are at the basis of what the detractors reclaim as the argument for suspension: the lack of users. By suspending time, human beings are being conditioned in their living mobility, with consequences that are far beyond this physical infrastructure and its occupied space. This is only a particular time case explored in this mean time.